2012
DOI: 10.1007/s00217-012-1753-4
|View full text |Cite
|
Sign up to set email alerts
|

The anti-staling effect of pre-gelatinized flour and emulsifier in gluten-free bread

Abstract: The use of gluten-free products is increasing since an increasing number of people (1-2 %) are suffering from Celiac disease and thereby need a gluten-free diet. Gluten-free bread tends to have shorter shelf life and quality compared with white wheat bread. In this study, 3 % (flour basis) of pre-gelatinized oat and barley flour as well as an emulsifier were added to a gluten-free mix to increase the water content by 1.5-2 %, affect the starch retrogradation and the formation of amylose lipid complex. The stal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 29 publications
(44 reference statements)
5
28
0
2
Order By: Relevance
“…Purhagen et al . () showed that the addition of emulsifiers could decrease bread hardening over the first 3 d. That finding coincides with the observations of Nunes et al . () after the addition of sodium stearoyl lactylate (SSL) and monoglycerides, but not with other emulsifiers, such as lecithin or diacetyl tartaric acid ester of mono‐ and diglycerides.…”
Section: Introductionsupporting
confidence: 90%
“…Purhagen et al . () showed that the addition of emulsifiers could decrease bread hardening over the first 3 d. That finding coincides with the observations of Nunes et al . () after the addition of sodium stearoyl lactylate (SSL) and monoglycerides, but not with other emulsifiers, such as lecithin or diacetyl tartaric acid ester of mono‐ and diglycerides.…”
Section: Introductionsupporting
confidence: 90%
“…; Purhagen et al. ). According to Gray and Bemiller (), amylopectin is the major factor in the retrogradation process but is not solely responsible for the observed change in texture.…”
Section: Introductionmentioning
confidence: 98%
“…Thermal treatment has numerous applications, it is a valuable tool for extending shelf-life of the flours by reducing the enzyme activity and moisture content of the lipid-rich fractions (Lehtinen et al, 2003;Purhagen, Sjöö, & Eliasson, 2011, 2012. Beside the biological effects, dry heat process has a significant impact on the techno-functional properties of flours.…”
Section: Introductionmentioning
confidence: 99%